Optimal Preheating Boosts Aluminium Weld Strength: Pemanasan Awal yang Optimal Meningkatkan Kekuatan Las Aluminium - Diyanto , Rizky Putra Ronal; Akbar , Ali (Universitas Muhammadiyah Sidoarjo, 2024)
Based on the conducted research, it is concluded that preheating has a significant impact on the tensile strength of welded aluminium 5083. Specifically, preheating at 40°C resulted in the highest ultimate tensile strength of 304.535 MPa, representing an 8.748% increase compared to the non-preheated specimen's 301.894 MPa. Conversely, preheating at 80°C led to a notable decline in tensile strength to 253.521 MPa, a decrease of 16.023%. These findings imply that moderate preheating can enhance the weld quality of aluminium 5083, while excessive preheating adversely affects it. This underscores the importance of optimizing preheating temperatures in welding processes to achieve desired mechanical properties. Further research is recommended to explore the underlying mechanisms affecting tensile strength at various preheating temperatures and to investigate the effects of preheating on other aluminium alloys. Highlight: Preheating at 40°C improves tensile strength by 8.748%. Excessive preheating at 80°C decreases tensile strength by 16.023%. Optimal preheating temperature crucial for weld quality in aluminium 5083. Keywoard: Aluminium 5083, Preheating, Tensile Strength, Welding, SMAW